High-speed X-ray PCI and XRD During Dynamic Fracture. (2017) - Chen, W.; Guo, Z.; Hudspeth, M.; Parab, N.; Sun, T.; Fezzaa, K.
Abstract: When a crack or a shear band propagates in a ductile material under impact loading, there is a severe stress concentration and/or strain localization near the tip of the discontinuity. It has been understood that the locally severe and fast deformation can lead to phase transformation and heat generation. The adiabatic conditions cause the local temperature to rise. However, it has been a challenge to experimentally measure the microstructural evolution, such as crystal d-spacing, texture evolution and material phase transitions, associated with the dynamic deformation and fracture process of ductile metallic materials. It is also a challenge for optical high-speed imaging techniques to image the details of the advancing crack tip with sufficient spatial resolution. In the dynamic experiments presented in this article, we used Kolsky bars integrated with a simultaneous X-ray phase contrast imaging (PCI) and diffraction (XRD) technique to study the dynamic deformation and fracture processes during high-rate loading. In such a Kolsky bar experiment, high-speed imaging of the specimen deformation and fracture processes and high-speed X-ray diffraction are recorded simultaneously in real time. The experimental setups and results on the dynamic fracture of an aluminum alloy and a bovine tibia bone are presented and discussed.